Chemotherapy-Induced Reduction of Neutrophil-to-Lymphocyte Ratio Is Associated With Better Survival in Pancreatic Adenocarcinoma: A Meta-Analysis. (27th November 2020) - Luo, Xin; Yu, Bo; Jiang, Nan; Du, Qiong; Ye, Xuan; Li, Huan; Wang, Wen-Quan; Zhai, Qing
Objectives: Numerous studies have suggested that an increase in neutrophil-to-lymphocyte ratio (NLR) before treatment is associated with worse survival in pancreatic adenocarcinoma (PAC). The aim of this study was to investigate the prognostic value of treatment-induced NLR change among PAC patients so as to better identify the characteristics of those who can benefit more from treatment. Methods: This meta-analysis was undertaken using the PRISMA statement. Previously published studies between the correlation of NLR change and patients' survival were searched in Pubmed, Embase, and Web of Science databases. RevMan 5.3 was used to conduct statistical analysis. Results: A total of 1213 patients with PAC from 6 retrospective studies were included in this meta-analysis. Four studies investigated the HR of pre-treatment NLR, demonstrating its prognostic impact on overall survival (OS) (HR = 2.21, 95%CI: 1.45-3.36). One study reported that an elevated post-treatment NLR was associated with poorer OS (HR = 1.28, 95%CI = 1.08-1.52). Pooled analysis indicated that NLR reduction might predict favorable survival in both the overall population (HR = 1.52, 95% CI: 1.34–1.73) and the subgroup treated with chemotherapy (HR = 1.50, 95% CI: 1.32-1.70). Conclusion: Treatment-induced NLR change can act as an early predictor for PAC. Patients with reduced NLR after chemotherapy are expected to have better survival.